Co-creating a person-centered creative engagement intervention for Parkinson's care - Spee, Blanca T. M.; Stap, Thieme B.; Plijnaer, Marjoke; Pasman, Gert; Zeggio, Sara; Duits, Annelien; Crone, Julia S.; Haeyen, Suzanne; Pelowski, Matthew; Bloem, Bastiaan R.; Koksma, Jan-Jurjen (Frontiers in Psychology, 2025)
BackgroundRecent research in the field of “Arts and Health” has demonstrated the beneficial impact of arts-based interventions on health and well-being across diverse populations. Recognizing their potential, especially in cases where conventional healthcare cannot address the multifaceted impact of conditions such as in Parkinson's disease (PD), our study advocates for an integrative approach in medical practice and neuroscience. We recommend incorporating learning environments from the design phase through long-term care. The arts offer a unique opportunity to create such environments. In this study, we specifically focus on individuals with PD, co-designing an intervention as a creative engagement learning environment and a PD-specific creative arts therapy. In this study, the narratives of those affected contribute as scientific knowledge, shaping care and increasing the intervention's relevance to participants' lives.MethodsWe used a participatory design-based research approach. Fourteen individuals with PD, along with three creative therapists and three researchers, collaborated through iterative design cycles to co-develop a creative arts therapy intervention. Qualitative data were collected through interviews, group reflections, and ethnographic observations. Data were analyzed using reflexive thematic analysis.ResultsThe co-creation process resulted in a 10-week creative engagement intervention delivered in a “creative playground” setting. Participants chose from multiple media and autonomously decided their creative activities. Guidance from the creative therapists was provided as needed to support individual engagement and guide reflection and learning processes. Narratives offered insights into the relevance of autonomy in care, the role of the arts, and the individuality of disease experience, resulting in seven key features of our intervention framework, which include (i) intervention structure (e.g., duration of the intervention and sessions), (ii) freedom in selection of creative media, (iii) environment as a creative playground, (iv) skills of creative therapists, (v) PD-specific considerations, (vi) financial considerations and logistics, and we list (vii) responsibilities of the Design Team.DiscussionThis study establishes an initial framework for a PD-specific creative arts therapy intervention designed as a creative engagement learning environment. Future research will focus on rigorously evaluating its effectiveness and exploring its scalability in diverse settings.